Effect of Water Stress and Hydrogen Peroxide and Potassium on the Growth and Yield of (Zea mays L.) - AL-Samerria, Ismail khalil; Rahi, Hamadallah Sulaiman; Abdullah, Asaad Kadhim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An experiment was conducted in the field, Department of field crops , College of Agriculture , University of Baghdad during fall season 2011. To study the effect of interaction of water stress and hydrogen peroxide and potassium on the growth and yield of maize plant cultivar Bohooth 106. It Included the study of three levels of water stresses of 40 , 60 and 80% of the available water , (D1 , D2 and D3) respectively, three levels of hydrogen peroxide of concentrations (0 , 15 and 30 Mm), and foliar application of potassium at the concentration of 3000 mg K. L-1 K2SO4 and without applied potassium.. Split – Split with RCBD design with three replications were used. The levels of water stresses occupied the main plots , potassium levels were in the sub- plots and the maize seed soaked with hydrogen peroxide occupied sub- sub plots. The results showed that water stress (D3) and H2O2 (30) Mm significatly reduced the plant propreties ( LSA , dry matter weight , 500 grain weight , grain and biological yield) whereas k significantly increased these plant propreties